Composite carrier as well as preparation method and application thereof

By using composite carriers, including porous structure molybdenum disulfide, zirconium metal organic frame and graphene, combined with carboxy groups, the problems of slow nitrogen removal rate and high energy consumption in the existing wastewater nitrogen removal technology are solved, and efficient wastewater nitrogen removal effect is achieved.

CN119774751AActive Publication Date: 2025-04-08SHANGHAI QIZHI NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510148228.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-08
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing wastewater denitrification technology requires a large amount of air, sludge and water return power consumption and exogenous organic carbon sources during the nitration and denitrification stages, resulting in a slower denitrification rate and waste of energy.

Method used

Using a composite support, including molybdenum disulfide with a porous structure, a zirconium metal organic frame is grown in situ in the porous structure of molybdenum disulfide, the surface is loaded with graphene, and carboxylic groups are connected to mix with activated sludge to improve the nitrogen removal efficiency of wastewater.

Benefits of technology

Through the use of composite carriers, the efficiency of wastewater denitrogenation is improved. The piezoelectric self-driven characteristics of molybdenum disulfide and the electron transfer ability of graphene promote the chemical reduction and biological denitrogenation of nitrate nitrogen, reducing energy consumption and sludge reflux.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater denitrification, and discloses a composite carrier and a preparation method and application thereof.The composite carrier comprises molybdenum disulfide of a porous structure, a zirconium metal organic framework grows in situ in the porous structure of the molybdenum disulfide, and graphene is loaded on the surface of the molybdenum disulfide. The composite carrier disclosed by the invention not only can be used as a place for nitrogen removal by microorganisms, but also can improve the nitrogen removal efficiency of the microorganisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater denitrification, and in particular to a composite carrier and a preparation method and application thereof. Background Art

[0002] Nitrogen removal from wastewater is the process of removing nitrogen from wastewater to prevent eutrophication of water bodies. It is generally divided into two methods: physical and chemical method and biological denitrification method. Physical and chemical denitrification methods include breakpoint oxidation method, air stripping or steam stripping method, and selective ion exchange method. In practice, the biological denitrification method of nitrification-denitrification is often used, that is, nitrifying bacteria in wastewater are used to oxidize nitrogen compounds into nitrates under aerobic conditions (nitrification stage), and then under anaerobic conditions (dissolved oxygen is less than 0.5 mg / L), denitrifying bacteria in wastewater are used to reduce nitrates into gaseous nitrogen and other final gas products and release them into the atmosphere (denitrification stage). However, in these two stages, a large amount of air and muddy water reflux power consumption and the addition of exogenous organic carbon sources are required, resulting in a slow denitrification rate and energy waste. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a composite carrier and a preparation method and application thereof. The composite carrier in the present invention can not only serve as a place for microorganisms to denitrify, but also improve the efficiency of microbial denitrification.

[0004] The present invention provides a composite carrier, which comprises molybdenum disulfide with a porous structure, a zirconium metal organic framework is in-situ grown in the porous structure of the molybdenum disulfide, and graphene is loaded on the surface of the molybdenum disulfide.

[0005] Furthermore, the surface of the composite carrier is also connected with a carboxyl group.

[0006] The present invention also provides a method for preparing the composite carrier, which comprises:

[0007] Step S1: immersing the porous molybdenum disulfide in a metal organic framework material precursor solution, performing hydrothermal treatment, washing, and drying to obtain an intermediate product;

[0008] Step S2: placing the intermediate product into a chemical vapor deposition furnace for vapor phase carbon deposition, and then treating it with plasma enhanced chemical vapor deposition, introducing oxygen into the plasma enhanced chemical vapor deposition method for treatment, setting the oxygen flow rate, treatment power, current, and voltage during treatment to obtain a composite carrier.

[0009] Furthermore, in step S1, the method for preparing the metal organic framework material precursor solution includes: dissolving zirconium oxychloride octahydrate and 1,3,5-trimethylolpropane in an organic solution and mixing them uniformly.

[0010] Furthermore, the organic solution consists of N,N-dimethylformamide and formic acid, and the ratio of N,N-dimethylformamide to formic acid is 1:1 by volume.

[0011] Furthermore, the ratio of zirconium oxychloride octahydrate to 1,3,5-trimethylbenzene carboxylic acid is (0.5-1.5) parts:(0.5-1) parts by mass.

[0012] Furthermore, the mass concentration of the zirconium oxychloride octahydrate in the organic solution is 0.5 g / 50 mL-1.5 g / 50 mL.

[0013] Furthermore, in step S1, the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution is 5 mg / mL-10 mg / mL.

[0014] Furthermore, in step S1, the temperature of the hydrothermal reaction is 110° C.-130° C., and the time of the hydrothermal reaction is 10 h-14 h.

[0015] Furthermore, in step S1, the specific process of washing includes: washing with N,N-dimethylformamide and methanol at least 3 times respectively.

[0016] Furthermore, in the step S1, the drying temperature is 50°C-70°C, and the drying time is 11h-13h.

[0017] Furthermore, in step S2, the specific method for performing gas-phase carbon deposition in the chemical vapor deposition furnace includes: placing the intermediate product into the chemical vapor deposition furnace, adjusting the gas flow rate of the gas-phase carbon source to 100mL / min-200mL / min, the reaction temperature to 1300℃-1500℃, and the reaction time to 0.5h-1h.

[0018] Furthermore, the heating rate to reach the reaction temperature is 4°C / min-6°C / min.

[0019] Furthermore, the gaseous carbon includes one or more of methane, acetylene, and ethylene.

[0020] Furthermore, in step S2, the flow rate of oxygen is 50mL / min-60mL / min, the processing power is 45W-55W; the current is not more than 1A and greater than 0.5A; the voltage is not more than 100KV and greater than 1KV.

[0021] The invention also provides application of the composite carrier in activated sludge for wastewater denitrification.

[0022] The embodiments of the present invention have the following technical effects:

[0023] 1. The composite carrier obtained in the present invention is used for mixing with activated sludge to improve the efficiency of wastewater denitrification. Specifically, molybdenum disulfide has piezoelectric self-driving characteristics. During the wastewater treatment process, electrons can be generated under the action of hydraulic disturbance vibration. The electrons can be transferred to the surface of microbial cells or nitrate nitrogen molecules to promote the chemical reduction of nitrate nitrogen and biological denitrification. In addition, the porous structure of molybdenum disulfide used in the present invention is not only conducive to increasing the specific surface area of ​​molybdenum disulfide, thereby facilitating more microorganisms to be loaded in its porous structure, but also conducive to the rapid transfer of generated electrons to the surface of microbial cells, further improving the efficiency of biological denitrification. On this basis, in order to avoid the structural collapse of the porous structure of molybdenum disulfide under the action of hydraulic pressure, a zirconium metal organic framework is in situ generated in the porous structure. First, the zirconium metal organic framework serves as a skeleton structure to support molybdenum disulfide. Second, it is conducive to the transfer of electrons in the porous structure, thereby facilitating more microbial cell surfaces in the porous structure to receive electrons. Third, the zirconium metal organic framework is corrosion-resistant. On this basis, the present invention also loads graphene on the surface of molybdenum disulfide. Graphene can not only transfer the electrons generated by molybdenum disulfide to the outside, and be used by the non-adsorbed microbial surface and nitrate nitrogen molecules in the sludge, but the graphene between the composite carriers can also form an electron transfer pathway in the activated sludge. It can be seen that graphene and the zirconium metal organic framework form an electron transfer route with molybdenum disulfide as the center, and electrons are transferred to the surrounding areas with molybdenum disulfide as the center, so that an electron transfer network is formed in the activated sludge. Finally, carboxyl groups are also connected to the surface of the composite carrier. The carboxyl groups can not only reduce the agglomeration between the composite carriers, but also facilitate the composite carrier to adsorb nitrate nitrogen molecules, thereby improving the efficiency of electron transfer.

[0024] 2. In the present invention, the graphene loaded on the surface of molybdenum disulfide can promote the transfer of electrons to the surrounding areas, and the amount of electrons generated by molybdenum disulfide is directly related to the magnitude of the water force transferred on the surface of molybdenum disulfide. Therefore, it is necessary to control the loading amount of graphene loaded on the surface of molybdenum disulfide to reduce the influence of graphene on the amount of electrons generated by molybdenum disulfide while ensuring the efficiency of electron transfer. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0026] In a first aspect, some embodiments of the present invention provide a composite carrier, which includes molybdenum disulfide with a porous structure, a zirconium metal organic framework is in-situ grown in the porous structure of the molybdenum disulfide, and graphene is loaded on the surface of the molybdenum disulfide.

[0027] In some embodiments, the surface of the composite carrier is further connected with a carboxyl group.

[0028] In a second aspect, some embodiments of the present invention further provide a method for preparing the composite carrier, the method comprising:

[0029] Step S1: immersing the porous molybdenum disulfide in a metal organic framework material precursor solution, performing hydrothermal treatment, washing, and drying to obtain an intermediate product;

[0030] Step S2: placing the intermediate product into a chemical vapor deposition furnace for vapor phase carbon deposition, and then treating it with plasma enhanced chemical vapor deposition, introducing oxygen into the plasma enhanced chemical vapor deposition method for treatment, setting the oxygen flow rate, treatment power, current, and voltage during treatment to obtain a composite carrier.

[0031] In some embodiments, in step S1, the method for preparing the metal organic framework material precursor solution includes: dissolving zirconium oxychloride octahydrate and 1,3,5-trimethylbenzene carboxylic acid in an organic solution and mixing them uniformly.

[0032] In some embodiments, the organic solution consists of N,N-dimethylformamide and formic acid, and the ratio of N,N-dimethylformamide to formic acid is 1:1 by volume.

[0033] In some embodiments, the ratio of zirconium oxychloride octahydrate to 1,3,5-trimethylbenzene carboxylic acid is (0.5-1.5) parts:(0.5-1) parts by mass.

[0034] In some embodiments, the mass concentration of the zirconium oxychloride octahydrate in the organic solution is 0.5 g / 50 mL-1.5 g / 50 mL.

[0035] In some embodiments, in step S1, the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution is 5 mg / mL-10 mg / mL.

[0036] In some embodiments, in step S1, the temperature of the hydrothermal reaction is 110° C.-130° C., and the time of the hydrothermal reaction is 10 h-14 h.

[0037] In some embodiments, in step S1, the specific process of washing includes: washing with N,N-dimethylformamide and methanol at least 3 times respectively.

[0038] In some embodiments, in step S1, the drying temperature is 50° C.-70° C., and the drying time is 11 h-13 h.

[0039] In some embodiments, in step S2, the specific method for performing vapor phase carbon deposition in the chemical vapor deposition furnace includes: placing the intermediate product into the chemical vapor deposition furnace, adjusting the gas flow rate of the vapor phase carbon source to 100mL / min-200mL / min, the reaction temperature to 1300℃-1500℃, and the reaction time to 0.5h-1h.

[0040] In some embodiments, the heating rate to reach the reaction temperature is 4°C / min-6°C / min.

[0041] In some embodiments, the gaseous carbon includes one or more of methane, acetylene, and ethylene.

[0042] In some embodiments, in step S2, the flow rate of oxygen is 50mL / min-60mL / min, the processing power is 45W-55W; the current is not more than 1A and greater than 0.5A; the voltage is not more than 100KV and greater than 1KV.

[0043] In a third aspect, some embodiments of the present invention also provide the use of the composite carrier in activated sludge for wastewater denitrification.

[0044] The following is a detailed description of the specific embodiments and comparative examples:

[0045] Embodiment 1:

[0046] (1) Preparation of metal organic framework material precursor solution: Weigh 1.2 g of zirconium oxychloride octahydrate and 1,3,5-trimethylformamide (0.8 g) and dissolve them in 50 mL of organic solution (the organic solution consists of formic acid and N,N-dimethylformamide, and the volume ratio of formic acid to N,N-dimethylformamide is 1:1), and stir ultrasonically for 1.5 hours.

[0047] (2) Preparation of porous molybdenum disulfide: Weigh 0.1mmol of ammonium molybdate tetrahydrate, add it to a 100mL beaker, then add 10mL of deionized water, fully dissolve the drug in a 50℃ water bath, then add 7mmol of thiourea, repeat the above heating operation to dissolve into a colorless and transparent precursor solution, then add 7mmol of silica with a diameter of 350nm to the beaker, and ultrasonicate for 30min to make the silica uniformly dispersed in the precursor solution. Then, stir at room temperature for 12h to allow the ions in the aqueous phase to fully contact the surface of the silica microspheres. Finally, place the obtained light blue suspension in a refrigerator and freeze it for 12h, then place the frozen solid sample in a freezer dryer (-40℃, 55Pa) and dry it for 15h. Scrape out the dried sample, grind it evenly, and calcine it at 500℃ in a nitrogen atmosphere in a tubular furnace for 4h. After the reaction is completed, the sample is treated with a 2M sodium hydroxide aqueous solution for 20 hours to remove the silica microspheres. Finally, the black powder sample is filtered and washed with deionized water for multiple times, and placed in a 50°C oven to dry to obtain porous molybdenum disulfide. In the present invention, the porous molybdenum disulfide can also be purchased commercially.

[0048] (3) The porous structured molybdenum disulfide was immersed in a metal organic framework material precursor solution, wherein the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution was 8 mg / mL. The mixture was evenly mixed, sealed in an autoclave at 130°C, and subjected to hydrothermal treatment for 13 hours. The mixture was washed three times with N,N-dimethylformamide and methanol respectively, and dried at 50°C for 12 hours to obtain an intermediate product.

[0049] (4) The intermediate product is placed in a chemical vapor deposition furnace for vapor phase carbon deposition, the methane gas flow rate is adjusted to 150 mL / min, the reaction temperature is 1400°C, the heating rate to reach the reaction temperature is 5°C / min, and the reaction time is 0.8 h. Then, a plasma enhanced chemical vapor deposition method is used for treatment, oxygen is introduced into the plasma enhanced chemical vapor deposition method for treatment, and the oxygen flow rate during treatment is set to 55 mL / min, the treatment power is 50 W, the current is 0.8 A, and the voltage is 2 KV to obtain a composite carrier.

[0050] Embodiment 2:

[0051] The preparation method of Example 2 is the same as that of Example 1, but when performing vapor phase carbon deposition in the chemical vapor deposition furnace in Example 2, the parameters used are: adjusting the methane gas flow rate to 200 mL / min, the reaction temperature to 1500°C, the heating rate to reach the reaction temperature to 4°C / min, and the reaction time to 1h. The other parameters in the preparation method of Example 2 are the same as those in Example 1.

[0052] Embodiment 3:

[0053] The preparation method of Example 3 is the same as that of Example 1, but when performing vapor phase carbon deposition in the chemical vapor deposition furnace in Example 3, the parameters used are: adjusting the methane gas flow rate to 100 mL / min, the reaction temperature to 1400°C, the heating rate to reach the reaction temperature to 6°C / min, and the reaction time to 0.5h. The other parameters in the preparation method of Example 3 are the same as those in Example 1.

[0054] Embodiment 4:

[0055] The preparation method of Example 4 is the same as that of Example 1, but when performing vapor phase carbon deposition in the chemical vapor deposition furnace in Example 4, the parameters used are: adjusting the methane gas flow rate to 200 mL / min, the reaction temperature to 1400°C, the heating rate to reach the reaction temperature to 5°C / min, and the reaction time to 0.8h. The other parameters in the preparation method of Example 3 are the same as those in Example 1.

[0056] Comparative Example 1:

[0057] The porous molybdenum disulfide was placed in a chemical vapor deposition furnace for vapor phase carbon deposition, the methane gas flow rate was adjusted to 150 mL / min, the reaction temperature was 1400°C, the heating rate to reach the reaction temperature was 5°C / min, and the reaction time was 0.8 h. Then, the plasma enhanced chemical vapor deposition method was used for treatment, oxygen was introduced into the plasma enhanced chemical vapor deposition method for treatment, and the oxygen flow rate during treatment was set to 55 mL / min, the treatment power was 50 W, the current was 0.8 A, and the voltage was 2 KV to obtain a carrier.

[0058] Comparative Example 2:

[0059] (1) Preparation of metal organic framework material precursor solution: Weigh 1.2 g of zirconium oxychloride octahydrate and 1,3,5-trimethylformamide (0.8 g) and dissolve them in 50 mL of organic solution (the organic solution consists of formic acid and N,N-dimethylformamide, and the volume ratio of formic acid to N,N-dimethylformamide is 1:1), and stir ultrasonically for 1.5 hours.

[0060] (2) The porous structured molybdenum disulfide was immersed in a metal organic framework material precursor solution, wherein the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution was 8 mg / mL. The mixture was evenly mixed, sealed in an autoclave at 130°C, and subjected to hydrothermal treatment for 13 hours. The mixture was washed three times with N,N-dimethylformamide and methanol, respectively, and dried at 50°C for 12 hours to obtain an intermediate product.

[0061] (3) The intermediate product is treated by plasma enhanced chemical vapor precipitation, oxygen is introduced into the plasma enhanced chemical vapor precipitation, and the oxygen flow rate during the treatment is set to 55 mL / min, the treatment power is 50 W, the current is 0.8 A, and the voltage is 2 KV to obtain a carrier.

[0062] Comparative Example 3:

[0063] (1) Preparation of metal organic framework material precursor solution: Preparation of metal organic framework material precursor solution: Weigh 1.2 g of zirconium oxychloride octahydrate and 1,3,5-trimethylformamide (0.8 g) and dissolve them in 50 mL of organic solution (the organic solution consists of formic acid and N,N-dimethylformamide, and the volume ratio of formic acid to N,N-dimethylformamide is 1:1), and stir ultrasonically for 1.5 hours.

[0064] (2) The porous structured molybdenum disulfide was immersed in a metal organic framework material precursor solution, wherein the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution was 8 mg / mL. The mixture was evenly mixed, sealed in an autoclave at 130°C, and subjected to hydrothermal treatment for 13 hours. The mixture was washed three times with N,N-dimethylformamide and methanol, respectively, and dried at 50°C for 12 hours to obtain an intermediate product.

[0065] (3) The intermediate product is placed in a chemical vapor deposition furnace for vapor phase carbon deposition, the methane gas flow rate is adjusted to 150 mL / min, the reaction temperature is 1400°C, the heating rate to reach the reaction temperature is 5°C / min, the reaction time is 0.8 h, and the carrier is obtained.

[0066] Comparative Example 4:

[0067] The preparation method of Comparative Example 4 is the same as that of Example 1, but when vapor phase carbon deposition is carried out in the chemical vapor deposition furnace in Comparative Example 4, the parameters adopted are: the methane gas flow rate is adjusted to 90 mL / min, the reaction temperature is 1300°C, the heating rate to reach the reaction temperature is 6°C / min, and the reaction time is 0.5h. The other parameters in the preparation method of Comparative Example 4 are the same as those in Example 1.

[0068] Comparative Example 5:

[0069] The preparation method of Comparative Example 5 is the same as that of Example 1, but when vapor phase carbon deposition is carried out in the chemical vapor deposition furnace in Comparative Example 5, the parameters adopted are: the methane gas flow rate is adjusted to 250 mL / min, the reaction temperature is 1500°C, the heating rate to reach the reaction temperature is 4°C / min, and the reaction time is 1h. The other parameters in the preparation method of Comparative Example 5 are the same as those in Example 1.

[0070] The carriers obtained from the embodiments and comparative examples were tested:

[0071] The carrier was mixed with activated sludge, and each 1g of carrier was mixed with 1000mL of activated sludge, and then placed in the biochemical system. The volume ratio of the mixed volume of the carrier and activated sludge to the volume of the biochemical system was 1:80, wherein the volume of the biochemical system was 1L, the biochemical denitrification of simulated wastewater was simulated, the influent TN was 60mg / L, the residence time was 14 hours, the temperature was room temperature (about 22°C), and the supernatant of the effluent was tested for nitrogen-related indicators. Among them, the activated sludge came from the activated sludge in the anoxic biochemical section of the chemical wastewater biochemical treatment system of Wuxi Hynix Semiconductor Materials Co., Ltd.

[0072] Results and Analysis:

[0073] Table 1 Treatment results of nitrogen-containing wastewater in Examples and Comparative Examples

[0074] — Inlet TN Outlet TN Total nitrogen removal rate (%) Example 1 60 3 95.00% Example 2 60 4.3 92.83% Example 3 60 4.5 92.50% Example 4 60 5.5 90.83% Comparative Example 1 60 30 50.00% Comparative Example 2 60 28 53.33% Comparative Example 3 60 16 73.33% Comparative Example 4 60 13 78.33% Comparative Example 5 60 17 71.67%

[0075] A composite carrier that can be used for denitrification of wastewater is successfully obtained by the method of the present invention. The molybdenum disulfide having a porous structure in the composite carrier obtained by the present invention has a piezoelectric self-driving characteristic, and generates electrons under the disturbance vibration of hydraulic force in wastewater treatment. The electrons can be transferred to the surface of microbial cells or nitrate nitrogen molecules, promoting the chemical reduction of nitrate nitrogen and biological denitrification, thereby facilitating the improvement of the rate of denitrification of wastewater. By comparing Examples 1 to 4 with Comparative Examples 1 to 5, it is found that the composite carrier obtained by the present invention has significant significance in denitrification of wastewater, and the nitrogen content of the wastewater treated by the composite carrier of the present invention is significantly reduced.

[0076] Since molybdenum disulfide with a porous structure is used, its porous structure can increase the specific surface area of ​​molybdenum disulfide, which is conducive to the adsorption of many microorganisms loaded in its porous structure, thereby helping to improve the efficiency of biological denitrification; however, the porous structure of molybdenum disulfide will collapse due to the action of hydraulic force. Therefore, in the present invention, a zirconium metal organic framework structure is also generated in situ in the porous structure, which can improve the stability of the porous structure on the one hand, and on the other hand, it can transfer electrons, which is conducive to more microbial cell surfaces in the porous structure receiving electrons, further improving the denitrification capacity in wastewater. It is verified by comparing Examples 1-4 with Comparative Example 1. When there is no zirconium metal organic framework in the porous structure, the structure of Comparative Example 1 may collapse, and the ability of electron transmission is reduced inside the porous structure. Therefore, the nitrogen conversion rate of Comparative Example 1 is significantly reduced compared with Examples 1-4.

[0077] Graphene is loaded on the surface of the porous molybdenum disulfide of the present invention. Graphene can not only transfer the electrons generated by molybdenum disulfide to the outside, and be used by the unadsorbed microbial surface and nitrate nitrogen molecules in the sludge, but also the graphene between the composite carriers can form an electron transfer pathway in the activated sludge; in addition, graphene and zirconium metal organic framework form an electron transfer route with molybdenum disulfide as the center, and electrons are transferred around molybdenum disulfide as the center, so that an electron transfer network is formed in the activated sludge, which is conducive to improving the electron transmission in the entire activated sludge, thereby improving the conversion rate of nitrogen in the wastewater. Comparison of Examples 1-4 with Comparative Example 2 shows that graphene can improve the conversion of nitrogen in wastewater.

[0078] When the graphene load on the surface of molybdenum disulfide is less, it will cause the electron transmission network to be poorly constructed, which is not conducive to the transmission of electrons in sludge; the amount of molybdenum disulfide electrons generated is directly related to the hydraulic size transferred on the surface of molybdenum disulfide, and when the graphene load is more, it will affect the hydraulic transmission, resulting in a decrease in the amount of electrons generated by molybdenum disulfide, and will also affect the conversion of nitrogen in wastewater. It can be verified by comparing Examples 1-4 with Comparative Examples 4-5. Therefore, only when the content of graphene loaded on the surface of molybdenum disulfide is appropriate, can the influence of graphene on the amount of electron generation of molybdenum disulfide be reduced on the basis of ensuring the efficiency of electron transmission.

[0079] Further comparison of Example 1 to Example 4 shows that when the methane ventilation volume increases, the reaction time can be increased, the heating rate can be reduced, and the reaction temperature can be increased. When the methane ventilation volume decreases, the reaction time can be reduced, the heating rate can be increased, and the reaction temperature can be reduced, thereby promoting uniform loading of graphene and reducing side reactions, which is beneficial for graphene to play its role.

[0080] Finally, a carboxyl group is connected to the composite carrier. The carboxyl group can not only reduce the agglomeration between the composite carriers, but also facilitate the composite carrier to adsorb nitrate nitrogen molecules, thereby improving the efficiency of electron transfer, which is verified by comparing Examples 1 to 4 with Comparative Example 3.

[0081] In summary, the composite carrier obtained by the present invention can not only serve as a place for microorganisms to denitrify, but also improve the efficiency of microbial denitrification.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A composite carrier, characterized in that The composite carrier comprises molybdenum disulfide with a porous structure, a zirconium metal organic framework is in-situ grown in the porous structure of the molybdenum disulfide, and graphene is loaded on the surface of the molybdenum disulfide.

2. The composite carrier according to claim 1, characterized in that The surface of the composite carrier is also connected with a carboxyl group.

3. The method for preparing the composite carrier according to any one of claims 1 to 2, characterized in that: The preparation method comprises: Step S1: immersing the porous molybdenum disulfide in a metal organic framework material precursor solution, performing hydrothermal treatment, washing, and drying to obtain an intermediate product; Step S2: placing the intermediate product into a chemical vapor deposition furnace for vapor phase carbon deposition, and then treating it with plasma enhanced chemical vapor deposition, introducing oxygen into the plasma enhanced chemical vapor deposition method for treatment, setting the oxygen flow rate, treatment power, current, and voltage during treatment to obtain a composite carrier.

4. The preparation method according to claim 3, characterized in that: In the step S1, the method for preparing the metal organic framework material precursor solution includes: dissolving zirconium oxychloride octahydrate and 1,3,5-trimethylolpropane in an organic solution and mixing them evenly.

5. The preparation method according to claim 4, characterized in that: The organic solution consists of N,N-dimethylformamide and formic acid, and the ratio of N,N-dimethylformamide to formic acid is 1:1 by volume; The ratio of the zirconium oxychloride octahydrate to 1,3,5-trimethylbenzene carboxylic acid is (0.5-1.5) parts: (0.5-1) parts by mass; The mass concentration of the zirconium oxychloride octahydrate in the organic solution is 0.5 g / 50 mL-1.5 g / 50 mL.

6. The preparation method according to claim 3, characterized in that: In the step S1, the mass concentration of molybdenum disulfide in the metal organic framework material precursor solution is 5 mg / mL-10 mg / mL; In step S1, the temperature of the hydrothermal reaction is 110°C-130°C, and the time of the hydrothermal reaction is 10h-14h; The specific process of washing includes: washing with N,N-dimethylformamide and methanol at least 3 times respectively; In the step S1, the drying temperature is 50°C-70°C, and the drying time is 11h-13h.

7. The preparation method according to claim 3, characterized in that: In the step S2, the specific method of performing gas phase carbon deposition in the chemical vapor deposition furnace includes: placing the intermediate product into the chemical vapor deposition furnace, adjusting the gas flow rate of the gas phase carbon source to 100 mL / min-200 mL / min, the reaction temperature to 1300° C.-1500° C., and the reaction time to 0.5 h-1 h; The heating rate to reach the reaction temperature is 4°C / min-6°C / min; The gas phase carbon includes one or more of methane, acetylene and ethylene.

8. The preparation method according to claim 3, characterized in that: In step S2, the flow rate of oxygen is 50mL / min-60mL / min, the processing power is 45W-55W; the current is not more than 1A and more than 0.5A; the voltage is not more than 100KV and more than 1KV.

9. Use of the composite carrier according to any one of claims 1 to 2 or the composite carrier obtained by the preparation method according to any one of claims 3 to 8 in activated sludge for wastewater denitrification.

Citation Information

Patent Citations

  • Biological potent agent based on molybdenum disulfide composite material as well as preparation and application of biological potent agent

    CN118289930A

  • Modified carbon felt electrode material and preparation method and application thereof

    CN118398752A

  • Preparation method and application of fabric for catalytically degrading sewage

    CN118563555A

  • Composite photocatalyst for degrading tetracycline, preparation method therefor and use thereof

    WO2021068570A1

Cited By

  • Desulfurizing agent as well as preparation method and application thereof

    CN120285763A

  • Graphene polyurethane biological carrier as well as preparation method and application thereof

    CN122276995A